Analisis Bibliometrik Dari Istilah ‘Salutogenesis Dalam Kebidanan’ - Ari Andriyani; Istri Bartini; Linawaty (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: The medical view of the entire maternal period calls into question the use of pathogenesisto frame maternity care services. Therefore, adopting a salutogenic model of maternal care can reducecare inequalities and improve the quality of maternity care provided. The concept of salutogenesis wasfirst introduced in the late 1970s by Antonovsky, who focused on the origins of good health rather thanthe origins of disease. Salutogenesis is an alternative school of thought that encourages healthcareprofessionals to adopt a more positive and health focused approach in providing perinatal care towomen. In the salutogenic approach, a woman's past experiences, both pleasant and unpleasant, arestrongly believed to contribute to her perception of life, well-being, and ability to cope with stressfulsituations such as the perinatal period.Objective: This study explores the topic of salutogenesis in obstetrics through the Google ScholardatabaseResearch Methods: This study uses bibliographic information from the Google Scholar article databasebetween 2000 and 2020 using a total sampling technique. Data was extracted using Publih Or Parish,VOS Viewer and Mendeley DesktopKeywords: salutogenesis, obstetrics, bibliometric, Publish Or Parish, VOSViewer